Differential transcriptome response to proton versus X-ray radiation reveals novel candidate targets for combinatorial PT therapy in lymphoma. (February 2021) - Sertorio, Mathieu; Nowrouzi, Ali; Akbarpour, Mahdi; Chetal, Kashish; Salomonis, Nathan; Brons, Stephan; Mascia, Anthony; Ionascu, Dan; McCauley, Shelby; Kupneski, Taylor; Köthe, Andreas; Debus, Jürgen; et al.
Abstract: Background and Purpose: Knowledge of biological responses to proton therapy (PT) in comparison to X-ray remains in its infancy. Identification of PT specific molecular signals is an important opportunity for the discovery of biomarkers and synergistic drugs to advance clinical application. Since PT is used for the treatment of lymphoma, we report here transcriptomic responses of lymphoma cell lines to PT vs X-ray and identify potential therapeutic targets. Materials and Methods: Two lymphoma cell lines of human (BL41) and murine (J3D) origin were irradiated by X-ray and PT. Differential transcriptome regulation was quantified by RNA sequencing for each radiation type at 12 hours post irradiation. Gene-set enrichment analysis revealed deregulated molecular pathways and putative targets for lymphoma cell sensitization to PT. Results: Transcriptomic gene set enrichment analyses uncovered pathways that contribute to the unfolded protein response (UPR) and mitochondrial transport. Functional validation at multiple time points demonstrated increased UPR activation and decreased protein translation, perhaps due to increased oxidative stress and oxidative protein damage after PT. PPARgamma was identified as a potential regulator of the PT transcriptomic response. Inhibition of PPARgamma by two compounds, T0070907 and SR2595, sensitized lymphoma cells to PT. Conclusions: Proton vs X-ray radiation leads to the transcriptional regulation of a specific subset of genes in line with diminished protein translation and UPR activation that may be due to oxidative stress. This study demonstrates that different radiation qualities trigger distinct cellular responses in lymphoma cells, and identifies PPARgamma inhibition as a potential strategy for the sensitization of lymphoma to PT.